Intensive multidisciplinary feeding intervention for patients with avoidant/restrictive food intake disorder associated with severe food selectivity: An electronic health record review. Issue 11 (10th September 2021) - Volkert, Valerie M.; Burrell, Lindsey; Berry, Rashelle C.; Waddle, Caitlin; White, Lydia; Bottini, Summer; Murphy, Meredith; Sharp, William G.
Abstract: Objective: Expert consensus increasingly recognizes intensive multidisciplinary intervention (IMI) as the standard of care to address chronic and severe feeding problems in pediatric populations. In this study, we examined the clinical presentation, intervention characteristics, and treatment outcomes for young children receiving IMI for avoidant restrictive rood intake disorder (ARFID) involving nutritional insufficiencies associated with severe food selectivity. Method: We followed the Strengthening the Reporting of Observational Studies in Epidemiology statement to conduct this retrospective chart review. The review focused on consecutive patients (birth to age 21 years) admitted to the IMI program over a 5‐year period (June 2014 to June 2019). Inclusion criteria required micronutrient insufficiencies (vitamins A, B12, C, D, E; folic acid; calcium; iron; and zinc) and chronic mealtime refusal behavior (e.g., turning head away from food/spoon, pushing or throwing spoon, crying, screaming, and leaving the table) associated with severe food selectivity. Results: Over the 5‐year period, 63 of the patients met study entry requirements. Of these, 60 patients (50 boys and 10 girls; mean age = 72 ± 39 months; range = 23–181) completed intervention (95% treatment completion rate). At discharge, dietary diversity improved by 16 new therapeutic foods (range: 8–22), rapid acceptance and swallowing of new foods exceeded clinical benchmarks (80% or > bites), and risk for nutritional inadequacies declined for this patient cohort. Discussion: Results of the current study support the benefits of IMI to increase dietary variety, improve mealtime behaviors, and enhance nutritional intake for children with ARFID presenting with severe food selectivity.